1996
DOI: 10.2105/ajph.86.9.1273
|View full text |Cite
|
Sign up to set email alerts
|

Low-level air pollution and hospital admissions for cardiac and cerebrovascular diseases in Helsinki.

Abstract: OBJECTIVES: This study investigated whether low concentrations of ambient air pollutants are associated with hospital admissions for ischemic cardiac and cerebrovascular diseases. METHODS: Associations between daily concentrations of sulfur dioxide, nitric oxide, nitrogen dioxide, ozone, and particulates and daily hospital admissions due to ischemic cardiac and cerebrovascular diseases were studied in Helsinki, Finland, 1987 through 1989. The regression analyses controlled for weather, day of the week, season,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(28 citation statements)
references
References 31 publications
4
23
1
Order By: Relevance
“…However, the ORs associated with a 10 g/m 3 increase in NO x were close to unity, indicating a lack of association regardless of statistical power. Previous studies on background levels of nitrous oxides and stroke have produced both negative [7,9,17,[19][20][21]24] and positive results [4-6, 13, 14, 16, 22, 23] , and have all used shared monitoring station data, whereas we used individually modeled data. Background concentrations of NO x have been shown to be an indicator for ultrafine particulate air pollution in an urban setting close to our study area [31] .…”
Section: The Results In Relation To Previous Studies and Issues For Fmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the ORs associated with a 10 g/m 3 increase in NO x were close to unity, indicating a lack of association regardless of statistical power. Previous studies on background levels of nitrous oxides and stroke have produced both negative [7,9,17,[19][20][21]24] and positive results [4-6, 13, 14, 16, 22, 23] , and have all used shared monitoring station data, whereas we used individually modeled data. Background concentrations of NO x have been shown to be an indicator for ultrafine particulate air pollution in an urban setting close to our study area [31] .…”
Section: The Results In Relation To Previous Studies and Issues For Fmentioning
confidence: 99%
“…The relation between hospital admissions for stroke and particulate air pollution is less clear; some researchers report an association [11][12][13][14][15][16] while others do not [17][18][19][20] . Associations have been observed between ozone, black smoke, CO, NO 2 and SO 2 for both stroke mortality and hospital admissions [6,9,[21][22][23] . In one study an association was observed between hospital admissions for ischemic stroke and ozone (in men), but not for particles [24] .…”
Section: Introductionmentioning
confidence: 99%
“…Virtanen, 1996), but, recently, Jousilahti et al (1996) reported some influence of chronic bronchitis on the risk of coronary disease.…”
Section: Figmentioning
confidence: 99%
“…The literature is still conflicted regarding the association between the level of PM 10 and stroke admissions. While some studies have shown significant associations between PM 10 and the overall number of stroke admissions,24 25 the results of other studies did not read significant levels 17 26–29. The discrepancy from previous studies regarding the association between stroke admissions and ADS may reflect the complexity of the topic.…”
Section: Discussionmentioning
confidence: 84%